Proses Peradilan Perbuatan Melawan Hukum Studi Kasus Penyerobotan Tanah - Vina Aprilia; Dimas Sahputra; Fisca Amanda Ramadhana; Parlaungan G. Siahaan; Dewi Pika Lumban Batu (Departement of Mathematics Education, 2023)
This research aims to help people know the procedures for resolving land grabbing disputes. Land grabbing is an unlawful act that can harm the land owner. Settlement of land grabbing disputes can be done through two channels, namely the non-litigation route and the litigation route. This research uses a legal method that combines doctrinal research (normative legal research) and socio-legal research (empirical legal research). The legal materials used in this research consist of primary legal materials and tertiary legal materials.